(untitled) (Global Journal of Human-Social Science, 2021)
While for the Church Marriage is a sacrament or covenant of life-long partnership of a man and a woman for their benefits procreation and education of children in the way of the Lord the Islamic system of marriage Nikah is a social legal and spiritual contract between the groom and bride which has a very significant role in society It is an act of Sunnah through which two families get closer Thus both Muslims and Christians value marriage and family but differ in the purpose structure and attributes which they associate with marriage from their different religious traditions In spite of their differences some of their members engage in interfaith marriages The challenges of such interfaith marriages and their prospects are of interest to us in this work We examine the dictates of scriptures and traditions to understand the theological implication of such marriages and with oral interviews and questionnaire administered we examine the practical issues involved Findings show that while some Christians take verses such as do not be un-equally yoked with unbelievers 2 Cor 6 14 as clear warning for Christians not to marry from among people of other faiths others rely on passages such as 1Corinthians 7 13-15 1Peter 3 1-6 to argue that the unbelieving husband or wife can become sanctified through the believing wife or husband